EFFECT OF MOLIBDENUM CONTENT AND HEAT TREATMENT ON CHARACTERISTICS OF TI-ZR-MO ALLOY - Tanuwijaya, Dian
Metals and alloys have been widely used as biomedical materials. It is estimated that 70-80% of biomedical implants are produced from metal materials. Metal biomaterials such as stainless steels, Co-Cr alloys, pure titanium and alloys were widely used because of their excellent mechanical properties. But sometimes metallic materials exhibit properties that can be poisonous and can be broken due to corrosion and mechanical damage. The development of titanium-based alloys for biomaterial applications continues. This is due to the good application of titanium alloys in the field of biomaterials based on their mechanical, physical, and biological properties. The objectives of this study were to study the effect of the addition of molybdenum element and the effect of heat treatment on characteristics of Ti-Zr-Mo alloys that contain no toxic elements for the human body. The experiment began with the manufacture of button alloys by the arc-melting method. The resulting alloy button consisted of four variations of composition, namely Ti-25Zr, Ti-20Zr-5Mo, Ti-20Zr-10Mo, and Ti-20Zr-15Mo. Sample button cut by wire-cutter. Then the sample with the four compositions were heat treated in the form of aging and quenching. Aging was carried out at 750oC and 850oC for 1 hour. Four variations of sample composition were produced with three types of alloys, namely as-homogenized, 750oC aging, and 850oC aging. After that, each sample was observed and tested to analysize their microstructure, phase, hardness, and corrosion rate. The observation of microstructure was conducted by optical microscope. The formed phase was known through the results of X-Ray Diffraction analysis. The sample hardness was tested by the Vickers Hardness Test. The corrosion rate was obtained by electrochemical test using a potentiostat in a simulated body fluid ringer lactate solution. The experiment results showed that Ti-Zr-Mo alloy properties highly effected by the level of molybdenum content and also heat treatment temperature. Higher molybdenum level can increase the stability of the beta phase in Ti-Zr-Mo alloys as seen from the increasing number of beta phases formed. At low Mo (Ti-20Zr- 5Mo), heat treatment produces a martensite phase, while at high Mo content (Ti- 20Zr-15Mo) heat treatment produces a metastable beta phase. The highest hardness value, 811.8 HVN, was obtained in alloys without the addition of Mo (Ti-25Zr) heat treated at 850oC followed by quenching. The lowest corrosion rate value, 0.000404 mm/year, was obtained at the addition of 10wt% Mo.